Perjodohan di masa kuliah: Antara tradisi keluarga dan otonomi individu mahasiswa - Wahyuni, Sri Nur (Maliki Interdisciplinary Journal, 2026)
This study examines the phenomenon of arranged marriage during university years as a form of interaction between family traditions, individual autonomy of students, and parental responsibility. In societal contexts, arranged marriage is not merely understood as a process of selecting a life partner, but also as part of a social system involving values, norms, and kinship structures that continue to persist. On the other hand, the development of higher education and the campus social environment encourages students to increasingly emphasize freedom in determining their life choices, including in personal relationships and marriage. This research employs a descriptive qualitative approach by examining various social perspectives related to the practice of arranged marriage. The findings reveal a tension between the individual desire for independent decision-making and the strong role of the family in influencing partner selection. Parents perceive arranged marriage as a form of moral responsibility to ensure their children’s future, while students prioritize personal compatibility and freedom of choice. However, the study also finds that arranged marriage is not always conflictual; rather, it can evolve into a negotiation process that leads to mutual agreement between both parties. Open communication and mutual understanding emerge as key factors in achieving a balance between individual autonomy and family considerations.